Institutional bricolage and the (re)shaping of communal land tenure arrangements: two contrasting cases in upland and lowland northeastern Laos - Suhardiman, Diana; Scurrah, N. (Elsevier, 2021)
This article examines the factors shaping communal land tenure and livelihood practices in two villages in Houaphan province, Northeastern Laos. It employs the concept of institutional bricolage to show how local actors combine communal tenure, state intervention, donor programs and local power relations to (re)shape formal rules and day-to-day land tenure and livelihood practices. In particular, it highlights how state territorial strategies in lowland and upland rural spaces have differently shaped state interventions in communal land use and access, producing hybrid forms of communal land management rules and practices. The two cases highlight different processes by which communal tenure is eroded or adapted in the process of state incorporation, raising questions about competing authorities over land and the interests and objectives of different actors in land administration. The village cases illustrate how local communities’ (in)ability to shape, adapt, and reproduce institutional rules and arrangements pertaining to access and use of communal land is closely interlinked with: 1) how farm households perceive communal land tenure in relation to their livelihood options and farming strategies; 2) how power relations among local communities and between local communities and state actors shape decision-making processes and distributional outcomes; and 3) the role of the state in sustaining and advancing its control over land and how this changes over time.